In-situ TEM study of the crystallization sequence in a gold-based metallic glass - Ivanov, Yu P.; Meylan, Carolina M.; Panagiotopoulos, Nikolaos T.; Georgarakis, Konstantinos; Greer, A. Lindsay (Elsevier, 2020)
The composition Au49Ag5.5Pd2.3Cu26.9Si16.3 (at.%) is of interest as the basis for the development of gold-based bulk metallic glasses for application in jewellery. In-situ heating in transmission electron microscopy (TEM) and differential scanning calorimetry (DSC, both conventional and fast) are used to obtain a comprehensive characterization of the decomposition on heating a melt-spun glass of this composition. Linking TEM with DSC over a range of heating rates 0.083‒2000 K s‒1, allows the sample temperature in the TEM heating stage to be calibrated. On heating up to melting, the glass decomposes in up to four stages: (1) complete transformation to single-phase nanocrystalline (Au,Cu)7Si; (2) grain growth of this phase; (3) precipitation of (Pd,Ag)Si, reducing the supersaturation of silicon in the (Au,Cu)7Si matrix; (4) with the precipitate phase remaining stable, decomposition of the matrix to a mixture of (Au,Ag)8Cu2, AuCu and Cu3Au phases. At all stages, grain diameters remain sub-micrometre; some of the stable nanocrystalline microstructures may themselves be of interest for applications. The characterization of the decomposition can assist in the optimization of the glass composition to improve tarnish-resistance, while retaining adequate glass-forming ability, formability in thermoplastic processing, and resistance to crystallization. For materials in general, the close correlation of in-situ TEM and DSC results should find wide use in characterizing complex transformation sequences.
Keywords: Metallic glass; In-situ transmission electron microscopy (TEM); Differential scanning calorimetry (DSC); Crystallization; Nanocrystalline alloys